Bone mineral density in patient admitted to Hospital Raja Perempuan Zainab II with proximal femur fracture - Abd Wahab, Noor Hidayah Abdullah@ (2016)
ABSTRACT Osteoporosis has been recognized as an established and well-defined disease that affects more than 8.9 million fractures annually worldwide. Most studies of fracture involving the proximal femur claim that generalized osteoporosis is the major etiological factor, although none has established a densitometric fracture threshold above which such fractures would not occur. Objectives This is a cross sectional analytical study with aims to identify the bone mineral density of elderly patients admitted for fracture proximal femur in an institution as assessed by Dual Energy X-Ray Absoptiometry (DXA) scan as well as to determine the biodemographics of the said profiles. Methodology Bone mineral density of 15 patients admitted for proximal femur fractures were evaluated using DXA scan.The T-score was further evaluated to see the significance of osteoporosis in these sujects.Results The mean age of the subject was 70 years old, and 80% were malays. 60% of them were non-milk consumer, and 80% were categorized under low socioeconomic group. Only 33% were a smoker. Bone density of neck of hip among the patients had the lowest median with -1.70 and interquartile range of 1.10. Then, it was followed by bone density for total hip and spine with median value of -1.60 and -1.40 respectively. Majority of the patients who involved in this study had their bonemineral density value as osteopenia. The highest osteopenia percentage was for the neck of hip, 66.7 %. Then it was followed by total hip and spine, 60% and 33.3 % respectively. The percentage of patients with osteoporotic group of BMD for total hip, spine and neck of hip were 6.7%, 33.3% and 20% respectively. 5 (33.3%) patients had their BMD total hip as normal, 5 (33.3%) patients for spine and 2 (20%) patient for neck of hip. Out of 15 subjects, only 1 who had all three BMD value of total hip, spine and neck of hip as osteoporosis. Fisher’s Exact test analysis found that there were no significant association between studied bio-demographic and bone mineral density at all measured sites. Conclusion This study found that there were no significant association between studied bio-demographic and bone mineral density at all measured sites. Majority of the patients who involved in this study had their bone mineral density value as osteopenia. The highest osteopenia percentage was for the neck of hip, 66.7 %, followed by total hip and spine, 60 and 33.3 % respectively. Keywords: Bone mineral density, DXA scan, osteoporosis, proximal femur fracture